Large-scale suppression of recombination predates genomic rearrangements in Neurospora tetrasperma. Issue 1 (December 2017) - Sun, Yu; Svedberg, Jesper; Hiltunen, Markus; Corcoran, Pádraic; Johannesson, Hanna
Abstract A common feature of eukaryote genomes is large chromosomal regions where recombination is absent or strongly reduced, but the factors that cause this reduction are not well understood. Genomic rearrangements have often been implicated, but they may also be a consequence of recombination suppression rather than a cause. In this study, we generate eight high-quality genomic data sets of the filamentous ascomyceteNeurospora tetrasperma, a fungus that lacks recombination over most of its largest chromosome. The genomes surprisingly reveal collinearity of the non-recombining regions and although large inversions are enriched in these regions, we conclude these inversions to be derived and not the cause of the suppression. To our knowledge, this is the first time that non-recombining, genic regions as large as 86% of a full chromosome (or 8 Mbp), are shown to be collinear. These findings are of significant interest for our understanding of the evolution of sex chromosomes and other supergene complexes. Genomic rearrangements can be either a cause or a consequence of large-scale suppression of recombination in a genome. Here, Sun et al. show that recombination may be suppressed in collinear genomic regions, and that inversions may accumulate over time in a derived manner.